(untitled) (Heritage, 2023)
The topic of this paper is the formal-structural and syntactic-semantic characteristics of comparative clauses in the function of sentence content condensers in the administrative-legal style. The corpus consists of a large number of examples excerpted from various constitutions in the period from 1835 to 1901 and laws from the 1940s. The main task of this paper is the analysis of constructions with the conjunctions nego štoand nego da based on their syntactic function and meaning in a concrete statement. In the paper, in addition to the descriptive approach, a transformation test was applied in order to understand the deep structures of the target constructions. There is a great lack of scientific research on this topic, discrepancies in terminology and classification of comparative constructions and a relatively small number of recorded target constructions with the indicated conjunctions. The frequency of use, i.e. the absence of these constructions in a larger number indicates the specificity of the language of that period and contributes to the description and analysis not only of the language of the Constitution and Laws from the 19th century, but also of the entire functional style and circumstances of that time. In the introductory part of the paper, we talk a little more about these constructions and their classifications in grammars, while the central part of the paper is devoted to the description of the grammatical, semantic and stylistic characteristics of given clauses and conjunctions.